2001
DOI: 10.1897/1551-5028(2001)020<1359:pbeope>2.0.co;2
|View full text |Cite
|
Sign up to set email alerts
|

Pyrene Bioaccumulation, Effects of Pyrene Exposure on Particle-Size Selection, and Fecal Pyrene Content in the Oligochaete Limnodrilus Hoffmeisteri (Tubificidae, Oligochaeta)

Abstract: The oligochaete Limnodrilus hoffmeisteri Cleparéde was exposed to sediment-amended pyrene (0-1,196 nmol/g dry wt) for 2, 5, and 10 d to investigate sediment particle-size preference, tissue pyrene bioaccumulation (using biota-sediment accumulation factor, BSAF), fecal pyrene concentrations (using fecal-sediment accumulation factor, FSAF), and pyrene biotransformation. In non-pyrene-amended sediment, L. hoffmeisteri preferentially ingested finer sediment particles (< 3.5 microns). However, pyrene concentrations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
27
1
2

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 21 publications
(33 citation statements)
references
References 28 publications
3
27
1
2
Order By: Relevance
“…The results revealed that sublethal effects to the worms occurred due to the high worm densities, which was consistent with previous studies (Lotufo et al, 2000;Millward et al, 2001;Mäenpää et al, 2009). Similar to the present study, sublethal toxicity was believed to be the reason for the decrease in bioaccumulation of pyrene in the oligochaetes Limnodrilus hoffmeisteri and L. variegatus (Millward et al, 2001;Mäenpää et al, 2009). Lotufo et al (2000) reported worms at high density were more susceptible to toxicant effects on their growth, and they suggested competition for food sources may be one of the reasons.…”
Section: Influence Of Bioturbation On Pah Toxicitysupporting
confidence: 92%
See 1 more Smart Citation
“…The results revealed that sublethal effects to the worms occurred due to the high worm densities, which was consistent with previous studies (Lotufo et al, 2000;Millward et al, 2001;Mäenpää et al, 2009). Similar to the present study, sublethal toxicity was believed to be the reason for the decrease in bioaccumulation of pyrene in the oligochaetes Limnodrilus hoffmeisteri and L. variegatus (Millward et al, 2001;Mäenpää et al, 2009). Lotufo et al (2000) reported worms at high density were more susceptible to toxicant effects on their growth, and they suggested competition for food sources may be one of the reasons.…”
Section: Influence Of Bioturbation On Pah Toxicitysupporting
confidence: 92%
“…Although reproduction was noted in some cases, survival of the worms was all close to 100 percent, thus reproduction was not the reason for the decline in worm weights in the present study. These results, which are consistent with the literature (Lotufo et al, 2000;Millward et al, 2001;Mäenpää et al, 2009), indicated that overcrowding may change organism susceptibility to contaminants, which in turn may alter sediment toxicity. Thus, future studies should take this into consideration when analyzing the effects of bioturbation on bioavailability of contaminants in sediments.…”
Section: Influence Of Bioturbation On Pah Toxicitysupporting
confidence: 92%
“…Input parameters were sediment-water distribution coefficients (K d ϭ f TOC ·K OC , with total organic carbon-normalized sediment-water distribution coefficient (K OC ) values estimated from logK OC ϭ logK OW Ϫ 0.21 [35]); coal and charcoal-water distribution coefficients (K S ) from Jonker and Koelmans [13]; and bioconcentration factors (estimated as BCF ϭ f lipid ·K OW ). Although Limnodrilus indeed probably has a slight preference for fine, low-density, organic carbon-enriched particles [36], incomplete gut clearance cannot have substantially contributed to the elevated BSAFs. After exposure, concentrations of several PCBs in worms inhabiting charcoalcontaining sediment should therefore be less than 10 g/kg (concentrations in extracts just above detection limits).…”
Section: Experimental Observations Versus Model Predictions: Competitmentioning
confidence: 98%
“…Although the role of organic carbon (OC) and other sediment composition factors, such as black carbon and sedimentary plant-derived carbon, have been well studied with respect to bioavailability (Rochne et al 2002;Cornelissen et al 2005;Kukkonen et al 2005;You et al 2006;Yang et al 2008), few studies have investigated the role that physical properties, such as sedimentary particle-size distribution, may play in this estimation (Cornelissen et al 1999;Millward et al 2001;Laak et al 2007). …”
mentioning
confidence: 99%
“…Moreover, selective ingestion of fine sediment by benthic organisms also make particle-size distribution an important factor affecting bioavailability of HOCs in sediment (Millward et al 2001). In addition, particle sizes equate to particle transport rates in the aquatic environment.…”
mentioning
confidence: 99%